Independent Village Development Based on Four Golden Pillars of Development - kholis, Nur; Mufidah, Nuril (Opción, 2019)
The purpose of this study is to find out the programs and activities of inde- pendent village development; and analyze the efficiency and effectiveness of programs and independent village development activities. This type of re- search is qualitative with research and development (R & D) approach. Data includes; independent village development programs and activities; and effi- ciency and effectiveness of independent village development. The program/ research objectives include; village head, village secretary, and other village officials, members of the village representative body (BPD), representatives of youth, religious and community organizations, and community members in general. Data was collected through in-depth interview techniques, observa- tion, and documentation. In data collection, in-depth interview techniques are used unstructured and open instruments. Data analysis techniques include; display data, data reduction, and temporary conclusions. The results of this study indicate that; First, independent village development programs include; efficient and accountable government management, village economic develop- ment, integrated environmental management, and community development with character. Meanwhile, activities carried out to develop independent vil- lages are the application of citizen service applications, preparation of per- mits, FGD SOP services; KUB. BUMDES, construction of village souvenir centers; building a waste charity center, promoting environmentally friendly tree planting, supporting TPQ, supporting youth/community/ religious activi- ties, making PKBM and TBM. Second, independent village development pro- grams and activities are quite efficient and effective, measured quantitatively and qualitatively.